The regulatory role of PGC1α‐related coactivator in response to drug‐induced liver injury. Issue 8 (11th July 2020) - Buler, Marcin; Naessens, Thomas; Mattsson, Johan; Morias, Yannick; Söderberg, Magnus; Robbins, Philip; Kärrberg, Lillevi; Svensson, Tor S.; Thulin, Petra; Glinghammar, Björn; Scarpulla, Richard C.; Andersson, Ulf
Abstract: PGC1α‐Related Coactivator (PRC) is a transcriptional coactivator promoting cytokine expression in vitro in response to mitochondrial injury and oxidative stress, however, its physiological role has remained elusive. Herein we investigate aspects of the immune response function of PRC, first in an in vivo thioacetamide (TAA)‐induced mouse model of drug‐induced liver injury (DILI), and subsequently in vitro in human monocytes, HepG2, and dendritic (DC) cells. TAA treatment resulted in the dose‐dependent induction of PRC mRNA and protein, both of which were shown to correlate with liver injury markers. Conversely, an adenovirus‐mediated knockdown of PRC attenuated this response, thereby reducing hepatic cytokine mRNA expression and monocyte infiltration. Subsequent in vitro studies with conditioned media from HepG2 cells overexpressing PRC, activated human monocytes and monocyte‐derived DC, demonstrated up to 20% elevated expression of CD86, CD40, and HLA‐DR. Similarly, siRNA‐mediated knockdown of PRC abolished this response in oligomycin stressed HepG2 cells. A putative mechanism was suggested by the co‐immunoprecipitation of Signal Transducer and Activator of Transcription 1 (STAT1) with PRC, and induction of a STAT‐dependent reporter. Furthermore, PRC co‐activated an NF‐κB‐dependent reporter, indicating interaction with known major inflammatory factors. In summary, our study indicates PRC as a novel factor modulating inflammation in DILI.